Content of the Right to Defence of Persons Affected by Domestic Violence (Law and Safety, 2025)
The concept of the content of the right to defence of subjective rights and freedoms of an individual from domestic violence is studied. It is noted that universality is a qualitative feature of the legal category of the right to defence ion. The legal nature of the right to defence is considered, the concepts of “right to defence ion” and “protection of rights” are analysed, which will allow better understanding and ensuring the protection and safeguarding of human rights and freedoms. The features that characterise the right to defence ion of victims of domestic violence are presented, and their role in its implementation is determined.In the conditions of legislative transformation and legal rethinking of modernity, great importance is attached to understanding of law, its nature, content, functions, and directions of influence on social relations. Therefore, there are grounds and a need to define the right to defence as a universal principle which forms a qualitatively new level of legislation not only at the federal but also at the regional level. It is indicated that the right to defence is a category in the theory of law which is an indicator of universality and preservation of its axiological significance for building a new system of legislation of Ukraine with a view to its development and compliance with international standards. The role of functions of law in the legal system cannot be underestimated. They, along with the principles of law, have become the starting structural components of this system.There are a lot of regulations developed to ensure a comprehensive approach to combating domestic violence and to promote the rights of victims of domestic violence through preventive measures, as well as to respond in a timely manner to the facts of domestic violence. Unfortunately, the problems remain and there are many of them.The starting point, the vector that will guide family policy, is the Strategy on Children’s Rights (2022–2027) “Children’s Rights in Action: from Stable Implementation to Joint Innovation”. It is determined that the primary task of the Strategy is to protect the interests of the child.
Keywords: content of the right to defence ion; legal nature of subjective civil rights; right to defence ion; domestic violence; domestic violence.